Search group algorithm: A new metaheuristic method for the optimization of truss structures. (June 2015) - Gonçalves, Matheus Silva; Lopez, Rafael Holdorf; Miguel, Leandro Fleck Fadel
Highlights: A new metaheuristic algorithm is proposed, the Search Group Algorithm (SGA). The SGA is successfully applied for the structural optimization of trusses. The SGA found the lightest structures available in the literature. The SGA outperformed the other metaheuristics in the analyzed examples. Abstract: This paper presents a new metaheuristic optimization method, the Search Group Algorithm (SGA), to deal with the optimization of truss structures. The effectiveness of the SGA is demonstrated through a selection of benchmark problems taken from the literature. Special attention is given to problems that involve topology optimization, discrete design variables and/or natural frequency constraints due to the complexities that they present. As the main conclusion of these numerical experiments, the SGA was able to provide the lightest structures ever found for 5 of the 6 examples investigated, to the best of the authors' knowledge. Moreover, it was also able to improve the statistics of the independent runs of the algorithm in most cases. These results emphasize the capabilities of the SGA in this field and encourage its further development and application to real problems in engineering.